Non-Formal Environment al Education and NGO-School Link for Environmental Awareness and Protection - Choudhury, Kabita (RESEARCH REVIEW International Journal of Multidisciplinary, 2021)
The protection and improvement of human environment is a major issue which affects the wellbeing of people and economic development throughout the world. In this rapidly changing man-made environment the need of restoring the originality of natural environment becomes a deep concern for the whole mankind. Lack of awareness, proper knowledge among the common people regarding the conservation of environment and its resources can lead to different socio-ecological and environmental problems. Unless the environmental education is reached to the grass root level and cover all sections of people no efforts on environmental protection can be expected. Therefore environmental education is designed as a lifelong process covering all sections of people and it is expected that environmental education will provide a fundamental understanding of bio-physica1 environmental problems confronting man, how these problems can be solved with sound knowledge and attitude. The life-long environmental education is known as the non-formal environmental education and it is designed for any age group, participating in social, economic, cultural development of the community. The present study tries to discuss the importance of NGOs and its linkage with the secondary schools in environmental awareness and protection as the N0n-governmental Organizations constitute an integral part of non-formal environmental education.